Antonio Gramsci : écrits politiques 1 : 1914-1920 - Gramsci, Antonio; Paris, Robert ([Paris] : Gallimard, 1974)
Biblitotheek François Vercammen
Frans
Meerdelige publicatie
Keywords: Partito Comunista Italiano (PCI).; communisme; Italië